2014
DOI: 10.1186/1471-2407-14-117
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of neutrophil-lymphocyte ratio in hepatocellular carcinoma: a meta-analysis

Abstract: BackgroundsNeutrophil-lymphocyte ratio (NLR) has recently been reported as a predictor of Hepatocellular carcinoma (HCC). However, its prognostic value in HCC still remains controversial. In this study, we aimed to evaluate the association between NLR and clinical outcome of HCC patients by performing meta-analysis.MethodsA comprehensive literature search for relevant studies published up to August 2013 was performed by using PubMed, Ovid, the Cochrane Library and Web of Science databases. Meta-analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
162
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(188 citation statements)
references
References 45 publications
10
162
1
5
Order By: Relevance
“…More than 600,000 people lose their lives due to HCC every year (3), and HCC is the third most frequent cause of cancer-associated mortality (4). Previous studies have demonstrated that the incidence rate of HCC has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…More than 600,000 people lose their lives due to HCC every year (3), and HCC is the third most frequent cause of cancer-associated mortality (4). Previous studies have demonstrated that the incidence rate of HCC has been increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Of those, NLR is one of the simplest and most effective inflammatory markers, and is associated with a poor prognosis in various types of cancer (25)(26)(27). A meta-analysis of the usefulness of NLR as a prognostic factor in HCC was recently published (28). The results indicated that the NLR cut-off value varied according to various treatments, such as transplantation, hepatectomy, RFA and TACE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the mechanism causing neutrophilia involves a systemic̸localized inflammatory response to a tumor or virus that leads to microcirculatory changes favorable for cancer progression or metastasis. It has also been suggested that a high NLR correlates with the strong invasion and activation of tumor-related macrophages (TAM) within the tumor, which promotes neutrophilia via cytokines such as interleukin (IL)-6 and IL-8 (28). It has also been demonstrated that neutrophils produce matrix metalloproteinase 9, which is involved in angiogenesis, thus promoting the development of tumors and chemokines, and vascular endothelial growth factor, thereby promoting tumor development and metastasis (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) was examined in many cancers and was found to be elevated in patients with advanced and aggressive disease (Lang et al, 2014;Ozdemir et al, 2014;Chang et al, 2014;Xiao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%